Enhancing Students’ Life Skills through Integrated Curriculum, Talent Placement, Enrichment, and Learning Motivation - Nur Azizatul Musyarofah; Kurnia Akbar (Advances Educational Innovation, 2025)
Purpose—This study examines the influence of curriculum integration, talent-based placement, extracurricular enrichment, and institutional support on students’ life skills through learning motivation in a pesantren-based educational context. Design/methodology/approach—The study employed a mixed-method sequential explanatory design. Quantitative data were collected from 180 MA students at Pondok Pesantren Modern Al-Amanah and analyzed using Partial Least Squares Structural Equation Modeling in SmartPLS. Qualitative data were obtained through interviews, observation, and documentation to explain and contextualize the quantitative findings. Findings- The results show that curriculum integration, talent-based placement, institutional support, and learning motivation significantly influenced students’ life skills. Talent-based placement was the strongest direct predictor of life skills, while extracurricular enrichment had the strongest effect on learning motivation. Learning motivation significantly mediated the effects of talent-based placement and extracurricular enrichment on students’ life skills but did not significantly mediate the effects of curriculum integration and institutional support. Research limitations/implications—This study was conducted in one pesantren-based institution; therefore, future research should involve multiple Islamic boarding schools and longitudinal designs to improve generalizability and causal interpretation. Practical implications—The findings suggest that modern pesantren should strengthen interest-and-talent-based placement, program-based enrichment, teacher mentoring, facilities, and school–pesantren collaboration to optimize students’ personal, social, academic-vocational, and digital life skills. Originality/value—This study contributes an integrated empirical model combining educational systems theory, self-determination theory, and the life skills framework to explain how pesantren-based education develops students’ life skills through both structural and motivational pathways.